Long-term episodic memory decline is associated with olfactory deficits only in carriers of ApoE-є4. (May 2016) - Olofsson, Jonas K.; Josefsson, Maria; Ekström, Ingrid; Wilson, Donald; Nyberg, Lars; Nordin, Steven; Nordin Adolfsson, Annelie; Adolfsson, Rolf; Nilsson, Lars-Göran; Larsson, Maria
Abstract: The ɛ4 allele of the Apolipoprotein E gene is a genetic risk factor for late-onset dementia of the Alzheimers' type (DAT), which is characterized by loss of both episodic memory and olfactory functions. Little is known about the possible role of ɛ4 in the association between ongoing episodic memory decline and olfactory deficits in the general population, but such information is relevant in determining the relevance of olfaction as a marker of DAT risk. The present study was based on a large, population-based sample (n=1087, aged 45–90 years, of which 324 were ɛ4-carriers). Episodic memory change rates were established using data collected every 5 years for a 10–20 year interval leading up to an olfactory assessment using the Scandinavian Odor Identification Test at the last wave of data collection. Participants were classified according to whether or not their episodic memory ability declined more rapidly than the age-typical norm (by >1SD). Our main result is that only in ɛ4-carriers was episodic memory decline associated with odor identification impairment. In individuals without ɛ4, odor identification was unrelated to episodic memory decline status. Follow-up analyses indicated that this moderation by ɛ4 was due to the olfactory nature of the identification test, and that the effect was not caused by 63 individuals with dementia. Our results suggest that the ɛ4 determines the functional association between ongoing episodic memory decline and olfaction. These findings are consistent with the notion that ɛ4-carriers with DAT, compared to non-carriers, display a cortical atrophy pattern that is more focused on mediotemporal lobe regions supporting olfactory and episodic memory functions. Olfactory and memory assessments might provide complementary information on mediotemporal atrophy prior to clinical dementia onset, but the ɛ4 should be considered when using olfactory assessment as an early-stage indicator. Highlights: First study on olfaction in elderly assessing both prior memory decline and genetics. Olfaction is impaired only in the presence of both episodic memory decline and ApoE-ɛ4. Olfaction is independent of episodic memory in non-carriers of ɛ4. Large, population-based sample validates odor-memory link in elderly with ɛ4. The ɛ4 might affect olfaction and episodic memory through similar mechanisms.